ENSINO DE HISTÓRIA EM CABO VERDE NO PÓS-INDEPENDÊNCIA: repensando a construção e valorização de uma identidade africana na Literatura Didática de história - MENDES, Washington Carlos da Silva (2018)
Cape Verde is a country of small dimensions when compared to most African countries, but its richness and importance are great. Being occupied and exploited by the Portuguese throughout several centuries, what made that from the beginning of its constitution there was an intersection of European and African elements. This configuration made Cape Verde one of the countries with one of the most mestizo populations in Africa. All this historical conjuncture left an identity struggle that will be analyzed here in the field of education and, more specifically, the teaching of history in the period after independence. Therefore, the objective was to present how the didactic literature of history has worked in the classroom on the question of identity constructions, the result of European and African inheritances in the country.